Case Report: The phantom gap: a case of congenital pericardial absence revealed by advanced imaging - Gou Junqi; Yao Fengyou; Liu Chaohui; Lang Mingjian; Jiang Xiaobo (Frontiers in Cardiovascular Medicine)
Congenital absence of the pericardium (CAP) is a rare cardiac anomaly with an estimated prevalence of <1:10,000. CAP results from premature atrophy of the left common cardinal vein during embryogenesis, leading to pericardial defects. In this report, the case of a 39-year-old male with recurrent left-sided chest tightness who was initially misdiagnosed with pulmonary embolism (PE) is presented. Anticoagulation failed to resolve symptoms, prompting advanced imaging and multidisciplinary team review, which confirmed CAP. Conservative management was chosen because of mild symptoms and low herniation risk. This case underscores the diagnostic complexity of CAP and highlights the role of advanced imaging in differentiating CAP from PE. Clinicians should consider CAP in patients with nonspecific cardiac symptoms and imaging findings of cardiac displacement or abnormal mobility.